Implementation Of Project-Based Learning Model To Improve Students' Creativity - Marnola, Ilham; Nate, Finte; Nurjani; Hiliyani (putrapublisher.org, 2025)
This study aims to analyse the application of the Project Based Learning (PjBL) model in improving the creativity of grade V students in science subjects with the topic of electrical energy at the Cendekia Integrated Islamic Elementary School (SDIT). This research uses the Classroom Action Research (PTK) method which is carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The research subjects were fifth grade students of SDIT Cendekia, with a total of 25 students. The research instruments included observation sheets, creativity questionnaires, and documentation. The results showed that the application of the PjBL model could improve students' creativity. In cycle I, the average percentage of student creativity reached 75% (moderately creative category), while in cycle II it increased to 85% (very creative category). Thus, Project Based Learning is effective in increasing the creativity of grade V students in science subjects. It is recommended for teachers to implement this model sustainably in learning science and other subjects.